Barriers of access to care in a managed competition model: lessons from Colombia (2010)
Background: The health sector reform in Colombia, initiated by Law 100 (1993) that introduced a managed competition model, is generally presented as a successful experience of improving access to care through a health insurance regulated market. The study’s objective is to improve our understanding of the factors influencing access to the continuum of care in the Colombian managed competition model, from the social actors’ point of view. Methods: An exploratory, descriptive-interpretative qualitative study was carried out, based on case studies of four healthcare networks in rural and urban areas. Individual semi-structured interviews were conducted to a three stage theoretical sample: I) cases, II) providers and III) informants: insured and uninsured users (35), health professionals (51), administrative personnel (20), and providers’ (18) and insurers’ (10) managers. Narrative content analysis was conducted; segmented by cases, informant’s groups and themes. Results: Access, particularly to secondary care, is perceived as complex due to four groups of obstacles with synergetic effects: segmented insurance design with insufficient services covered; insurers’ managed care and purchasing mechanisms; providers’ networks structural and organizational limitations; and, poor living conditions. Insurers’ and providers’ values based on economic profit permeate all factors. Variations became apparent between the two geographical areas and insurance schemes. In the urban areas barriers related to market functioning predominate, whereas in the rural areas structural deficiencies in health services are linked to insufficient public funding. While financial obstacles are dominant in the subsidized regime, in the contributory scheme supply shortage prevails, related to insufficient private investment. Conclusions: The results show how in the Colombian healthcare system structural and organizational barriers to care access, that are common in developing countries, are widened by both the insurers’ use of mechanisms that limit the utilization and the public healthcare providers’ change of behavior in a competition environment. They provide evidence to question the promotion of the managed competition model in low and middle-income countries.